Physiotherapy clinical educators' perceptions of student fitness to practise. Issue 1 (December 2017) - Lo, Kristin; Curtis, Heather; Keating, Jennifer; Bearman, Margaret
Abstract Background Health professional students are expected to maintain Fitness to Practise (FTP) including clinical competence, professional behaviour and freedom from impairment (physical/mental health). FTP potentially affects students, clinicians and clients, yet the impact of supervising students across the spectrum of FTP issues remains relatively under-reported. This study describes clinical educators' perceptions of supporting students with FTP issues. Methods Between November 2012 and January 2013 an online survey was emailed to physiotherapy clinical educators from 34 sites across eight health services in Australia. The self-developed survey contained both closed and open ended questions. Demographic data and Likert scale responses were summarised using descriptive statistics. The hypotheses that years of clinical experience increased clinical educator confidence and comfort in supporting specific student FTP issues were explored with correlational analysis. Open text questions were analysed based on thematic analysis. Results Sixty-one percent of the 79 respondents reported supervising one or more students with FTP issues. Observed FTP concerns were clinical competence (76%), mental health (51%), professional behaviour (47%) and physical health (36%). Clinicians considered 52% (95% CI 38-66) of these issues avoidable through early disclosure, student and clinician education, maximising student competency prior to commencing placements, and human resources. Clinicians were confident and comfortable supporting clinical competence, professional behaviour and physical health issues but not mental health issues. Experience significantly increased confidence to support all FTP issues but not comfort. Student FTP issues affects the clinical educator role with 83% (95% CI 75-92) of clinicians reporting that work satisfaction was affected due to time pressures, emotional impact, lack of appreciation of educator time, quality of care conflict and a mismatch in role perception. Educators also considered that FTP issues affect service delivery and impact on those seeking health care. Conclusions Strategies to support student FTP have potential to positively impact on students, clinicians and clients. Collaboration between these stakeholders is required, particularly in supporting mental health. Universities are strategically placed to implement appropriate support such as communication support.